Step-by-step explanation:
f(x) = x^2 + 5x – 6 becomes g(x) if we replace each x in f(x) with (x+4):
g(x) = (x+4)^2 + 5(x+4) - 6
This can be expanded: g(x) = x^2 + 8x + 16 + 5x + 20 - 6, or
g(x) = x^2 + 13x + 30
Answer:
a-1/4 , b- 0.17, c-2/9
Step-by-step explanation: you have to read the number line carefuly.
Answer:
2
Step-by-step explanation:
The text translates to:
5x + 2 < 13
which simplifies to
x < 11/5
the greatest integer that does this is 10/5, a.k.a. 2
<h3> Hope this attachment helps u</h3>
Answer:
x=27
Step-by-step explanation:
(2x-18)+(4x)=180 bc its a straight line
simplify
6x-18=180
-18 -18
6x=162
divide
x=27